The Economic Transition of the Balkan Area and the Competitive Framework of the Albania - Ronza, Luigi di (Richtmann Publishing, 2011)
This paper shows the results of an internship the commercial office of the Embassy of Italy in Tirana. The analysis of thecauses of the bad economic performance in the Balkan area can be referred to several phenomena like: the statistical phenomenon ofIllusion, the Keynesian theory, the credit market working, the European trade, the structural change shown by Olivier J. Blanchard andof the Cross-cultural transition. Albania has undertaken, with many difficulties, the European-road. Some progresses have been made,but even if some macroeconomic indicators can be read with a positive value, the real economy is heavily dependent on abroad. The countryshows a weak economy, the industry is lacking, a growing development has occurred in the service sector, and it is still the agriculture thatpulls the country's economy.